Pasar Ulak Karang Pasca Gempa Kota Padang Tahun 2009 - 2023 - Harahap, Ronaldo; Najmi, Najmi (Jurnal Kronologi, 2025)
This research examines the development of Ulak Karang Market after the earthquake in Padang City which affected traders' income on 30 September 2009 - 2023. After the earthquake, Ulak Karang Market experienced damage to 2 kiosk buildings and 4 stone table buildings. The damage that occurred included damage to the roof, ceiling, pillar supports, and cracks in the building walls. As a result, there is a decrease in traders' income. To overcome this problem, the Government is taking various steps to increase the income of traders at Ulak Karang Market. The aim of this research is to find out what the condition of the snakehead fish market was after the 2009 earthquake. And how the snakehead fish market developed after the earthquake in Padang City in 2009 - 2023. This research is a type of qualitative research that uses historical research methods. includes four stages, namely: heuristics (collecting data), source criticism (criticizing data sources), interpretation (interpreting, analyzing and explaining past events) and historiography (the process of writing a historical work). The results of the research show that after the 2009 earthquake, damage occurred to 2 kiosk buildings and 4 stone table buildings, more specifically the Ulak Karang market trading shops, totaling 12 traders. As a result, traders' income has decreased due to the minimal number of consumers and visitors at Ulak Karang Market. Then in 2023, the revitalization of the Ulak Karang Market will be carried out through PEMKO Padang which is supported by the Indonesian Ministry of Trade through Assistance Task funds for the 2023 fiscal year amounting to IDR 3 billion.